Judicial Review due to Bankruptcy Law on State-Owned Enterprises (Persero) and Workers - Muhammad Ali Adnan; Atika Sunarto (LEGAL BRIEF, 2020)
Bankruptcy is a general confiscation covering all debtor assets for the benefit of all creditors. In other words, bankruptcy is the time when the debtor is no longer able to pay all debts that are due. State-Owned Enterprises (BUMN) is a company in the form of a limited liability company (Persero) which is wholly, mostly or partly owned or managed by the government and directly controlled by the government. Workers or laborers are people who work and receive wages or other forms of remuneration. The research made in making scientific papers is normative legal research. Normative legal research or it can be called library research is research that saya learning in the form of documents, using a variety of secondary data, namely regulations in legislation, court decisions set by judges, and legal theories. The data source used to write scientific papers is secondary data sources. This secondary data source takes data that comes from existing journals, established laws and regulations. Secondary data also logged all documents that were informed.